Effects of floral display and abiotic environment on the foraging activity of bees on Kallstroemia pubescens (Zygophyllaceae). Issue 6 (1st November 2020) - Sandoval-Molina, Mario A.; Flórez-Gómez, Nathalia A.; Pérez-Botello, Antar M.; Hinojosa-Díaz, Ismael A.; Reyes-Tovar, Jessica M.; Ayala, Ricardo
Abstract : Foraging activity of bees depends on a combination of their biology, floral traits attractive for bees and environmental factors. We carried out this study to determine whether the variation of floral aperture, floral display and environmental factors throughout the day influence the foraging activity and composition of bee visitors in Kallstroemia pubescens (G. Don) Dandy. This research was conducted at the Chamela Biological Station, UNAM, Jalisco, Mexico. During anthesis, we collected bees and recorded the foraging behavior hourly. We measured hourly the environmental factors (temperature, relative humidity, and light intensity), floral aperture, floral display and floral reward. Using generalized linear mixed-effects models we tested which of the factors have more influence on floral aperture and foraging activity. To determine the dissimilarity of the species composition between the hours sampled, we used a one-way analysis of similarity (ANOSIM). We found that light intensity and humidity affected the floral aperture. Likewise, floral aperture, light intensity, temperature and time of day had a higher influence on the frequency of visitation and composition of bee species. When flowers were fully open, we recorded a greater number of bees and species. We observed two types of foraging behavior: bees collecting resources from the top of the flower (pollen gatherers) and bees within the flower avoiding the anthers and stigma (nectar gatherers). The total number of pollen gatherers recorded during our observations was greater than nectar gatherers, suggesting that this is the main floral reward. The species that had the pollen gathering behavior were mainly big bees, Apis mellifera and Exomalopsis zexmeniae, these are the potential pollinators because of their direct contact with the reproductive parts of the flower. Our results show floral aperture and environmental factors in combination influenced the foraging activity of bees, promoting changes in bee community composition throughout the day.